2022
DOI: 10.28933/ijsmr-2022-06-1505
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for shoulder pain and injury in elite badminton players

Abstract: Research ArticleIJSMR (2022) 5:25 Mechanism for shoulder pain and injury in elite badminton playersPurpose: to detect the mechanisms for shoulder pain and injury during forehand overhead stroke using the questionnaire and 2D video analysis. Methods and Materials: Participants were 48 university badminton players (aged 18-22) with national tournament level who had no current shoulder injuries. A questionnaire investigation and a forehand overhead clear test were performed. The angle of arm slot at the moment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In addition, shoulder injuries are often experienced by badminton players due to repetitive overhead movements, such as smashes and serves, which can lead to overuse injuries such as rotator cuff tendinitis. Studies by (Zhou et al, 2022) have identified that these repetitive movements without adequate rest can increase the risk of shoulder injuries. Back injuries are also a concern, especially among players who perform a lot of smashes and serves, where excessive rotation and extension of the spine can lead to injury.…”
Section: A Injuries In Badmintonmentioning
confidence: 99%
“…In addition, shoulder injuries are often experienced by badminton players due to repetitive overhead movements, such as smashes and serves, which can lead to overuse injuries such as rotator cuff tendinitis. Studies by (Zhou et al, 2022) have identified that these repetitive movements without adequate rest can increase the risk of shoulder injuries. Back injuries are also a concern, especially among players who perform a lot of smashes and serves, where excessive rotation and extension of the spine can lead to injury.…”
Section: A Injuries In Badmintonmentioning
confidence: 99%